RECONSTRUCTION OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM BASED ON ARTIFICIAL INTELLIGENCE TO FORM RELIGIOUS DIGITAL CITIZENSHIP IN THE SOCIETY 5.0 ERA - Hasmiza Hasmiza; Waslun; Abu Bakar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the reconstruction of the Islamic Religious Education (PAI) curriculum based on Artificial Intelligence (AI) to systematically cultivate religious digital citizenship in the Society 5.0 era. Employing a qualitative case study approach, data were collected through in-depth interviews with PAI teachers, curriculum developers, and school administrators, complemented by participatory classroom observation and curriculum documentation analysis. Data analysis followed the Miles and Huberman interactive model, with credibility established through source and method triangulation. Findings reveal that the current PAI curriculum has organically integrated AI tools into its learning practices, producing observable indicators of religious digital citizenship; however, this achievement remains structurally incidental rather than intentionally designed. In response, this study proposes a four-dimensional curriculum reconstruction framework encompassing philosophical repositioning grounded in Islamic epistemology, cross-domain digital ethics content redesign, a three-phase AI-mediated pedagogical sequence (ta'aruf, tafakkur, tahqiq), and competency-based assessment aligned to religious digital citizenship outcomes. This reconstructed model contributes directly to SDG 4 (Quality Education) by advancing inclusive and character-forming religious education, and to SDG 16 (Peace, Justice, and Strong Institutions) by equipping students to engage digital public life with Islamic ethical grounding and moral discernment.